Clinical nurses’ beliefs, knowledge, organizational readiness and level of implementation of evidence-based practice: The first step to creating an evidence-based practice culture - Yoo, Jae Yong; Kim, Jin Hee; Kim, Jin Sun; Kim, Hyun Lye; Ki, Jung Suk (PLOS ONE, 2019)
Background This study aimed to identify clinical nurses’ evidence-based practice (EBP) knowledge, beliefs, organizational readiness, and EBP implementation levels, and to determine the factors that affect EBP implementation in order to successfully establish EBP. This study was conducted at a university-affiliated tertiary hospital located in a provincial area in Korea. The research design was based on Melnyk and Fineout-Overholt’s Advancing Research & Clinical Practice through Close Collaboration model as the first step. Methods A descriptive and cross-sectional design was conducted and a convenience sample of 521 full-time registered nurses from an 849-bed tertiary hospital were included. Structured questionnaires were used to assess EBP knowledge, EBP beliefs, organizational culture & readiness and EBP implementation. Data were analyzed using SPSS V 25.0 by using descriptive and inferential statistics and hierarchical multiple regression was performed to determine the factors affecting the implementation of EBP. Results Our findings showed that the clinical nurses had a positive level of EBP beliefs, but the level of EBP knowledge, organizational readiness and EBP implementation were insufficient. EBP knowledge, beliefs, and organizational readiness were significantly positively correlated with EBP implementation. In the final model, EBP knowledge and organizational readiness were significant predictors of EBP implementation; the model predicted 22.2% of the variance in implementation. Conclusions Based on these results, the main focus of the study was the importance of individual nurses' efforts in carrying out EBP, but above all efforts to create an organizational culture to prepare and support EBP at the nursing organization level. In the initial process of introducing and establishing EBP, nurse administrators will need to minimize expected barriers, enhance facilitators, and strive to build an infrastructure based on vision, policy-making, budgeting, excellent personnel and facilities within the organization.